The association between drug therapy problems and blood pressure control of patients with hypertension in public health center setting - I Nyoman Wijaya, - (PagePress Publications, 2022)
Background: Patients with hypertension are at risk of experiencing Drug Therapy Problems (DTPs). However, few have studied the pattern of DTPs in Indonesian public health center (PHC) and how it affected the blood pressure control.